Local Election and Reinforcement Democracy in the Indonesian State System - Raharusun, Anthon (Faculty of Law Cenderawasih University, 2017)
The direct election of Regional Head and Deputy Regional Head directly and democratically by the people is a political process of the Indonesian nation towards a more democratic, transparent, accountable and responsible political life and administration. Therefore, in order to ensure the implementation of election of Regional Heads and Regional Representatives at a time of quality and meet the degree of healthy competition, the requirements and procedures for election of Regional Head shall be stipulated in separate laws and regulations. In general it is said that the direct election of the regional head is more democratic. There are at least two reasons why the idea of direct election is considered necessary: First; to open the door for the appearance of the head of the region in accordance with the will of the majority of the people themselves. Second; to maintain government stability so as not to be easily dropped in the middle of the road. Practice during the regime of Law Number 22 Year 1999 regarding Regional Government, indicates that the election through DPRD mechanism is often opposed even not in accordance with the will of the majority of people in the region. In this connection, there are several reasons why the direct Election of Regional Head (Local Election) is important for the development of democracy in Indonesia are: First; direct regional head elections allow for the strengthening of democracy at the local level, in particular the development of political legitimacy. This is based on the assumption that the elected Head of Region has a strong mandate and legitimacy, because it has the support of the peoples voice directly reflecting the configuration of political forces and the interests of the constituents of voters. This legitimacy is very important for the governing government. Second; Direct Regional Head Election is expected to be able to build and realize local accountability and strengthening of democratic values in Indonesian state administration system.